One Health Approach in Traditional Milk Production as a Part of Steps towards SDGs - Jevtic, Marija; Belic, Branislava; Glavas–Trbic, Danica (European Journal of Sustainable Development, 2020)
The production of milk and cheese assumes activities in the field of agricultural production, veterinary health, and the use of milk and dairy products has public health significance, and can be viewed through the "one health" concept. The aim of the paper is to underline public health and sustainability significance of interconnection among agriculture, veterinary and technology. Production of hard cheese with added value from milk produced in organic and self-sustaining systems research the risks, advantages and possibilities of traditional cheese production and focused on creating conditions for organic milk and hard cheese with added value production, with precisely defined conditions: isolating land plots, livestock farms and processing facilities from possible sources of pollution, water quality, harmonized development of plant and animal production and the capability of producers for organic agriculture with the obligation to constantly innovate knowledge. The new products ensure the employment and livelihood of people in the countryside, the economic prosperity of small family farms, link the activities in the field of veterinary health and agricultural production, contribute to the development of risk-management technology, healthy chooses and compatible with SDGs. Keywords: One Health approach, Traditional Milk Production, sustainability, Healthy Choices, SDGs